National Working Group on the RE-AIM Planning and Evaluation Framework: Goals, Resources, and Future Directions - Harden, Samantha M.; Strayer, Thomas Edward; Smith, Matthew Lee; Gaglio, Bridget; Ory, Marcia G.; Rabin, Borsika; Estabrooks, Paul A.; Glasgow, Russell E. (Frontiers in Public Health, 2020)
The National Working Group on RE-AIM Planning and Evaluation Framework (herein Workgroup) was established in 2004 to support the application of the framework and advance dissemination and implementation science (D&I). Workgroup members developed and disseminated products and resources (and continue to do so) to advocate for consistent application of RE-AIM and allow for cross study comparisons. The purpose of this paper is to summarize key Workgroup activities, products, and services (e.g., webinars, consultations, planning tools) and enhance bidirectional communication between the Workgroup and RE-AIM users. The ultimate goal of this work is to serve as a forum for dissemination to improve the balance between RE-AIM user demand (needs) and the currently limited RE-AIM Workgroup supply (consultation and resources) to demonstrate and expand the utility of RE-AIM as a D&I planning and evaluation framework. A summary of resources is provided as well as specific examples of how the Workgroup has been responsive to user needs.